2021
DOI: 10.3390/curroncol28030170
|View full text |Cite
|
Sign up to set email alerts
|

Re-Irradiation for Locally Recurrent Lung Cancer: A Single Center Retrospective Analysis

Abstract: The treatment of locally recurrent lung cancer is a major challenge for radiation-oncologists, especially with data on high-dose reirradiation being limited to small retrospective studies. The aim of the present study is to assess overall survival (OS) for patients with locally recurrent lung cancer after high-dose thoracic reirradiation. Thirty-nine patients who were re-irradiated for lung cancer relapse between October 2013 and February 2019 were eligible for the current retrospective analysis. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…As mentioned before, a major problem of thoracic re-irradiation is toxicity and its inter-study comparability. Most of the included studies referred to the 4th version of the CTCAE classification except for Oghuri [23] and Grambozov [24], who used versions 3 and 5, respectively. With respect to the main OARs, i.e., lung and esophagus, these various editions of the CTCAE are similar.…”
Section: Toxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned before, a major problem of thoracic re-irradiation is toxicity and its inter-study comparability. Most of the included studies referred to the 4th version of the CTCAE classification except for Oghuri [23] and Grambozov [24], who used versions 3 and 5, respectively. With respect to the main OARs, i.e., lung and esophagus, these various editions of the CTCAE are similar.…”
Section: Toxicitymentioning
confidence: 99%
“…Severe (grade 3-4), acute, and late toxicities were observed in 0% [30]-39% [3] and 0% [25,29] to 12 % [3], respectively. Seven studies reported therapy-related mortality between 2% [24,27] and 14% [26].…”
Section: Toxicitymentioning
confidence: 99%
See 3 more Smart Citations